PENGARUH PROFESIONALISME, PENGETAHUAN MENDETEKSI KEKELIRUAN, DAN ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS OLEH AUDITOR PADA KAP DI SURABAYA - DESIANA, . (: 2303-1719)
Audit of financial statements is necessary for the company to serve as the basis for decision making. The financial statements can be reliabel and relevant information in making decisions, having been audited by external auditors. In this case the auditor’s duty to determine the materiality level judgement client’s financial statements. Judgement of a bad audit can lead to the risk af audit in determination of materiality level judgement. Materiality level judgement of auditor’s can be influenced by professionalism, knowledge for errors, and professional ethics. The aim of this study was to examine the effect of professionalism, knowledge for errors, and professional ethics on materiality level judgement in the auditing process of financial statement. The study design is quantitative with the hypothesis. Data were obtained by survey questionaires, which were completed by accountants who work at Registered Public Accountants in Surabaya started from senior up to partner leel and obtained as many as 48 respondents from 19 KAP. Sampling techniques using convenience sampling. Data were analyzed using multiple regression analysis. The result of this study showed that professionalism, and knowledge for errors have significant influence to materiality level judgement, while the professional ethics not influence to materiality level judgement.